O papel da liquidez/iliquidez no retorno das ações: análise do mercado brasileiro no período entre 1995 e 2010 - Justen Junior, Ari Aloisio (2012)
The influence of liquidity / illiquidity on the return on assets has been widely researched in last years, from both individual assets and market perspectives.Given the evidence that the liquidity / illiquidity is a multidimensional measure and that a single proxy is not sufficient to assess it, this study, aiming for greater robustness, seek to evaluate the role of same using different measures, making sure that its use influence the results. This paper analyzes the influence of liquidity / illiquidity in stock returns in the Brazilian market, using the measures proposed by Amihud (2002) and Liu (2006) beyond traditional measures such as trading volume, number of trades, spread and turnover. To that we use data from December, 1994 to April 2010 of the stocks traded on the Bolsa de Valores, Mercadorias e Futuros de São Paulo (BOVESPA). The results obtained through the estimation of the model using the measure of illiquidity for the actions allow to concluding that the expected illiquidity has positive impact on the monthly return, supporting the first hypothesis of the original study by Amihud (2002), which suggests that the expected stock return is an increasing function of expected illiquidity. Regarding the second hypothesis tested, the unexpected illiquidity (residual) showed negative impact on return, confirming the hypothesis that unexpected illiquidity has a negative effect on the stock price, that is, the illiquidity is priced in the Brazilian market. In another way, the estimation results of the model that used the measure of Liu (2006) for the actions, demonstrated that the variables expected liquidity and unexpected liquidity were not significant in explaining returns. As to the model that has used variables of market liquidity the estimation with the measure of Amihud (2002) did not present significance for the variables expected market iliquidity and unexpected market illiquidity. Differently, the model estimated using the variables of market liquidity for the stock returns presented positive impact to the variable expected market liquidity. In turn, the variable unexpected market liquidity showed negative impact on monthly returns. It can be inferred that in Brazil, a country with great heterogeneity in the liquidity, the market liquidity risk of lose space for the individual liquidity risk.